2007
DOI: 10.1016/j.reprotox.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal blood and organ toluene levels in rats following acute and repeated binge inhalation exposure☆

Abstract: Inhalation of organic solvents is a persistent form of drug abuse with particular concern being the abuse of inhalants by women of child-bearing age. While studies have begun assessing postnatal outcomes of offspring exposed prenatally to inhalants, relatively little is known about the distribution of toluene in blood and body tissues of pregnant, inhalant-abusing women, or in the fetuses. The present study assessed the tissue toluene levels attained following brief toluene exposures using a pre-clinical rat m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…These findings are consistent with those of a previous study assessing blood and organ toluene levels in a rat model of maternal inhalant abuse [Bowen et al 2007b]. Toluene exposures (8,000 ppm or 12,000 ppm for 15, 30, or 45 min) occurred twice daily from gestational day 8 (GD8) through GD20.…”
Section: Pharmacodynamics/pharmacokinetics Of Toluene Teratologysupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with those of a previous study assessing blood and organ toluene levels in a rat model of maternal inhalant abuse [Bowen et al 2007b]. Toluene exposures (8,000 ppm or 12,000 ppm for 15, 30, or 45 min) occurred twice daily from gestational day 8 (GD8) through GD20.…”
Section: Pharmacodynamics/pharmacokinetics Of Toluene Teratologysupporting
confidence: 91%
“…Maternal blood and tissue, placenta, amniotic fluid, and fetal brain specimens were obtained after dams were sacrificed on GD20. Maternal blood toluene levels increased with inhaled toluene concentration and exposure duration [Bowen et al 2007b] Similarly, toluene levels in placenta and amniotic fluid increased with exposure duration, and higher toluene levels were found in fetal brains as the vapor concentrations increased. While toluene levels in most maternal tissues were reported to be higher than in maternal blood, the levels in amniotic fluid were not.…”
Section: Pharmacodynamics/pharmacokinetics Of Toluene Teratologymentioning
confidence: 85%
See 1 more Smart Citation
“…Some of these factors including route of administration, dosage and timing of exposure, influence the toluene developmental toxicity and impact on biobehavioral maturation of offspring. To our knowledge, relatively fewer studies have examined gross dysmorphology after repeated, high-dose binge patterns of prenatal toluene exposure [8,10,11,19,54]. In our previous study, prenatal binge exposure to repeated 15-min bouts of toluene (8,000 or 12,000 ppm) twice a day (30-min total daily exposure) from Gestation Day 8 (GD8) through GD20, resulted in significantly increased numbers of minor malformations, “runting” and fetal or postnatal death [8].…”
Section: Introductionmentioning
confidence: 99%
“…14) The concentration of toluene within organisms starts decreasing rapidly immediately after exposure, but it can accumulate easily in tissues high in lipid content. 14,15) The lipid content of fetuses is generally lower than that of adults, 16) which may be one of the causes of the difference in the blood toluene level between mother rats and fetuses found by this study. Although blood lipid level was not measured in this study, it has been shown that lipid soluble compounds such as polychlorinated biphenyl (PCB) was parallel to the serum lipid level.…”
Section: Results Of Concentration Measurement Of Toluene In Fetal Bloodmentioning
confidence: 62%